Lay Public View of Neuroscience and Science-Based Brain Health Recommendations in Slovenia - Tomat, Nastja; Perovnik, Matej; Vidmar, Gaj; van Midden, Vesna; Fabjan, Sara; Hawlina, Hana; Trol, Dolores; Holnthaner, Alina; Krajnc, Sebastijan; Grešak, Maruša; Žerdin, Liza; Vidmar, Judita; et al. (Frontiers in Public Health, 2021)
Background Brain health is one of the cornerstones of a long and full life. Active care for brain health and reduction of lifestyle-related risks for brain disorders may be a key strategy in tackling the growing prevalence of mental and neurological illnesses. Public knowledge, perception and preventive behavior need to be considered in the planning of effective strategies for brain health promotion. Our research is the first effort aimed at assessing Slovenian lay public knowledge, search and use of scientific information about the brain and care for brain health. Methods An online survey was used to gather data for descriptive and associative statistical analyses of a sample of Slovenian public (n = 2568) in August 2017. Participants with formal brain-related education were excluded, leaving the remaining sample of lay public (n = 1012). Demographic characteristics and information regarding participants’ perceived importance and knowledge of and engagement in preventive behaviors were collected, and key associative analyses were carried out. Results The majority of respondents (89%) considered brain health to be important. Over a third (39%) considered their knowledge of the brain as sufficient relative to their needs. Most of the respondents identified science recommended practices to be important for brain health. No recommendation was followed daily by the majority of the respondents, primarily due to declared lack of time (59%) and lack of information (32%). Information was obtained primarily from television (38%), followed by newspapers and magazines (31%), internet (31%), and direct conversations (27%). However, the highest rated preferred source of information was experts’ lectures. One third of our sample struggled with trustworthiness of information sources. Female gender and older age were associated with higher frequency of healthy practices. Personal or familial diagnoses of brain disorders were not associated with higher frequency of behavior in favour of brain health, but did affect available time and perceived value of preventive practices. Conclusions Our research provides an initial insight into the Slovenian lay public’s perceptions, knowledge, and brain health-promoting behavior. Our findings can inform future strategies for science communication, public education and engagement, and policy-making to improve lifelong active care for brain health.